Instituto interactivo de reforestación ambiental Soacha - Sibaté - Plan parcial: la hoja 2060 (2019)
As a general proposal the partial plan an urban piece included in a territory of 60 hectares between the limits of Soacha and Sibaté more specifically north side of the reservoir of the muña which are distributed in 7 areas of action seeking territorial balance and solving more relevant problems generating an organic urbanism of transition according to the concepts of the new urbanism. Specifically, a series of equipment distributed in an area of action focused on environmental improvement and the competitive impulse of Sibaté with the department oriented to social progress and the T.O.D. It is the result of the analyzes and diagnoses that were carried out in the work area under the connection with development plans that are implemented in the Sibaté POT and the concepts of the new urbanism. This research covers the history of the territory, the conformation and future projections, which have had and will have an impact in the place, which generate an important footprint for the benefit in the growth of this, from the moment of the intervention, the proposal will be for the favor of the region and its inhabitants. As conclusive of a result, the architectural project is born having an impact on the departmental, regional and municipal scales.